2020
DOI: 10.1016/j.rmed.2020.106218
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein cholesterol as a factor affecting virus clearance in covid-19 patients

Abstract: Objective There were COVID-19 patients with SARS-COV-2 nucleic acid long-term positive. This article aims to understand the relevant factors that affect SARS-COV-2 clearance time. Methods The clinical data of 115 COVID-19 patients with SARS-COV-2 nucleic acid positive time exceeding 14 days were collected retrospectively, and the relationship between clinical characteristics, chest CT scans, blood cells, biochemical indicators, and the time of viral nucleic acid turning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…In this context, high-density and low-density lipoprotein cholesterol and total cholesterol levels were reported to be significantly decreased in COVID-19 patients (Ressaire, Dudoignon, Moreno, Coutrot, & Dépret, 2020; G. Wang et al, 2020 ). Low cholesterol levels were correlated with a higher risk of developing severe events or longer recovery times in some studies ( X. Ding et al, 2020 ; Ressaire, Dudoignon, Moreno, Coutrot, & Dépret, 2020 ; G. Wang et al, 2020 ), but not in another one ( Tanaka et al, 2020 ).…”
Section: Cholesterol Reducing Drugs and Ace2mentioning
confidence: 86%
“…In this context, high-density and low-density lipoprotein cholesterol and total cholesterol levels were reported to be significantly decreased in COVID-19 patients (Ressaire, Dudoignon, Moreno, Coutrot, & Dépret, 2020; G. Wang et al, 2020 ). Low cholesterol levels were correlated with a higher risk of developing severe events or longer recovery times in some studies ( X. Ding et al, 2020 ; Ressaire, Dudoignon, Moreno, Coutrot, & Dépret, 2020 ; G. Wang et al, 2020 ), but not in another one ( Tanaka et al, 2020 ).…”
Section: Cholesterol Reducing Drugs and Ace2mentioning
confidence: 86%
“…Increased mortality was observed in patients with low total cholesterol, LDL-C, and/or HDL-C levels at admission to the hospital and in these very ill patient’s lipid levels continued to decline during the hospitalization ( 28 , 36 , 38 , 41 , 43 , 44 , 45 ). A single study reported that the time to develop a negative RT-PCR test for SARs-CoV-2 was increased in patients with low HDL-C levels ( 46 ). Finally, HDL isolated from patients with COVID-19 infections displayed a blunted ability to protect against TNF alpha induced increases in endothelial cell permeability, vascular endothelial-cadherin disorganization, and apoptosis ( 39 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinsmentioning
confidence: 99%
“…In particular, the HDL-C level decreased according to the severity of the cytokine storm [ 10 ]. HDL-C is an important factor affecting virus clearance in COVID-19 patients [ 11 ]. A lower serum HDL-C level was significantly associated with the longer clearance of SARS-CoV-2, approximately 32.5 days after the onset of COVID-19 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HDL-C is an important factor affecting virus clearance in COVID-19 patients [ 11 ]. A lower serum HDL-C level was significantly associated with the longer clearance of SARS-CoV-2, approximately 32.5 days after the onset of COVID-19 [ 11 ]. Other studies showed that the average time from the beginning of symptom onset to the first negative test of a throat swab SARS-CoV-2 was 9.5–11 days [ 12 ].…”
Section: Introductionmentioning
confidence: 99%